The modified Si-Jun-Zi Decoction attenuates colon cancer liver metastasis by increasing macrophage cells - Jin-Yong Zhou; Min Chen; Cun-En Wu; Yu-Wen Zhuang; Yu-Gen Chen; Shen-Lin Liu (BMC, 2019)
Abstract Background The modified Si-Jun-Zi Decoction (SJZ), a Chinese medicine formula, is clinically used against multiple malignancies including colorectal cancer (CRC). This study aims to evaluate the effect of modified SJZ on CRC liver metastasis and identify the therapeutic mechanisms. Methods Human CRC cells with GFP fluorescence were transplanted into Balb/c nude mice spleens. Modified SJZ, 5-fluorouracil or the combined treatment was given for 3 weeks. CRC liver metastasis was measured by fluorescence imaging and plasma cytokines were analyzed. Furthermore, the effects of administration time and doses for the modified SJZ were investigated in nude mice. Results Modified SJZ could increase the survival rate and reduce CRC liver metastasis in the nude mice model. Plasma GM-CSF level was elevated. Three weeks of treatment with the modified SJZ at the full dose (45 g/kg) could significantly increase the number of macrophages but not neutrophils in the spleen. Conclusions These results indicate that modified SJZ can inhibit CRC liver metastasis by activating the innate immune system, providing a complementary and alternative therapy for CRC.